Assessment of Carpal Tunnel Syndrome risk among designers performing digital design activities - Mohd Juzad, Kodsiah (2023)
Carpal Tunnel Syndrome (CTS) is a significant occupational disease among intense computer users such as designers and other professionals. Adverse musculoskeletal problems such as numbness, tingling, weakness or muscle injury in the hand and fingers can result from CTS. Designers are prone to CTS due to working for long hours nature in poor posture. The aim of this study is to determine risk of CTS among designers that working on design work digitally using computer in a cross-sectional study. A total of 225 designers who met the inclusion criteria participated in the survey that deployed Phalen's test to screened for CTS as well as Boston Carpal Tunnel Questionnaire (BCTQ). Rapid Office Strains Assessment (ROSA), NASA Task Load Index (TLX) and the Fuzzy Delphi method were among the instruments used in this study. Respondents included graphic, multimedia, industrial, automotive, interior, and computer aided design (CAD) designers, architects, and design engineers. The study found a prevalence of 20% of CTS among these designers. In this study, the following risk factors were associated with CTS: side job more than 6 hours per week (OR: 2.81, 95% CI 1.17-6.74) and graphic designers (OR: 2.08, 95% CI: 1.06-4.10). In this study designers' workplace was assessed using the Rapid Office Strain Assessment (ROSA), it was found that 58.82% of designers who participated in the assessment scored 5 or higher (ROSA) that indicates designers need to take ergonomic measures on the workstation in the future. In this study, designers with positive Phalen’s test took Boston Carpal Tunnel Questionnaire (BCTQ) to accesses severity and symptoms of CTS that affecting these creative population. In terms of psychological risk, mental workload (MLW) was highest in this population, with a mean score of 63.48 for NASA TLX. A high value (> 60) was associated with mental workload in the post-test. The design task, which must be completed within a tight time frame, ranked first for “effort” in the pre-test and post-test, indicating that the design task requires both a physical and mental workload. The MWL result indicates that designers' unique way of working, which requires eustress to accelerate creativity, contributes to the risk of CTS. Carpal Tunnel Syndrome Risk Among Designers Model was established using multiple regression modelling in SmartPLS 4 in order to determine the relationship between work organisation (B=0.66, T=2.81, P<0.05) and stress responses after work (B=0.28, T=3.56, P<0.05) factors with CTS outcome. The two predictors significantly predicted the outcome and both mentioned factors contribute 52.1% to risk of CTS in design population. The model was validated by eight experts using the fuzzy Delphi method and reached expert’s consensus of 98% on all 14 items. The experts agreed that stress responses after work was significantly reflects the risk factor of design population in this study. The experts agreed that the model suitability to be used as guide for designers and employers to educate and spreading awareness to employers and designers on risk of CTS. Stress responses after work factor that consist of more than 6 hours of side job a week variable, was both found significantly associated with both MLR and Regression model. Therefore, it can be concluded that more than 6 hours of side job in a week is the significant risk factor among within design community where it’s become novelty of this research. Raising awareness among designers is important to protect their talented hands, because hands are another asset of these professionals, along with their creative minds. This research could lead to a better understanding of the unique relationship between designers' practises and the risk of CTS for future prevention planning.